Isolation, identification, and evaluation of lactic acid bacteria with probiotic potential from traditional fermented sour meat - Zhao, Jiayi; Zhao, Jinshan; Zang, Jinhong; Peng, Chuantao; Li, Zhaojie; Zhang, Peng (Frontiers in Microbiology, 2024)
Sour meat is a popular traditional fermented product and is a rich source of novel strains with probiotic potential. In this study, we aimed to assess the probiotic potential of lactic acid bacteria (LAB) strains isolated from fermented sour meat. Firstly, the microbial diversity of sour meat from four different areas in China was analyzed. The results showed that LAB were predominant in all samples. Subsequently, LAB were isolated from sour meat and a series of in vitro probiotic tests were carried out. A total of 130 bacterial strains with dissolved calcium were obtained and 10 strains showed a range of 89–97% survival in an acidic environment and high tolerance to bile salts. The ranges of hydrophobicity and auto-aggregation of 10 strains were 4.85–80.75% and 1.58–84.2%, respectively. Besides, all 10 strains exhibited high antimicrobial activity and antioxidant activity, of which, DZ24 possessed the strongest free radical scavenging (45.1%) and anti-lipid oxidizing ability (90.3%). Furthermore, DZ24 was identified as Lactiplantibacillus plantarum by 16S rRNA gene sequencing. Moreover, the fermentation indexes showed that DZ24 could rapidly reduce the pH to 4.14 and showed high salt and nitrite resistance and antioxidant ability. All the above experimental results indicate that Lactiplantibacillus plantarum DZ24 promise a suitable probiotic candidate for future applications in the fermented functional meats.